Идентификация характеристик системы резистивно-индукционного нагрева для транспортировки хлора методами математического моделирования - Ярымбаш, Сергей Тимофеевич; Ярымбаш, Дмитрий Сергеевич; Килимник, Ирина Михайловна; Литвинов, Дмитрий Александрович (НТУ "ХПИ", 2010)
The definition method of the resistive induction heating system parameters of the chlorine pipeline is presented. This method is considered system design features. It’s based on the electric and thermal model realization by the final elements and iterations methods, with the system characteristics identification by variables division and approximation methods, which are provided the high calculation accuracy and efficiency.
The identification of the resistive induction heating characteristics for the chlorine pipeline transportation by the mathematical modeling methods
Keywords: энергосбережение; трубопровод; процесс тепловой; температура; процесс электромагнитный; модель электротепловая; аппроксимация